2003
DOI: 10.1108/09600030310478793
|View full text |Cite
|
Sign up to set email alerts
|

Continuous improvement and learning in the supply chain

Abstract: This paper reports on research into continuous improvement and learning in logistics. It is generally acknowledged that in today's dynamic and turbulent environment, firms have to develop capabilities that allow them to be very flexible and agile, and at the same time, be able to incorporate new (product and process) technologies that enable them to develop and exploit better practices in supply chains. This flexibility and agility calls for companies to increase their effectiveness, exploit synergies, and lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 12 publications
0
38
0
11
Order By: Relevance
“…In addition, technologies drive innovation because they improve communication and collating information as a source and driver of innovation, fostering further collaboration (Soosay and Hyland, 2004). Hyland et al (2003) identified major capabilities that contribute to innovation in the supply chain context: the management of knowledge; the management of information; the abilities to accommodate and manage technologies; and the ability to manage collaborative operations. In this paper, innovativeness is considered in the supply chain context since new processes introduce a tendency towards implementation of integrated information technology systems with supply chain partners in pursuit of more integrated supply chains and supply chain performance.…”
Section: Literature Review and Hypotheses Development 21 Innovativenessmentioning
confidence: 99%
“…In addition, technologies drive innovation because they improve communication and collating information as a source and driver of innovation, fostering further collaboration (Soosay and Hyland, 2004). Hyland et al (2003) identified major capabilities that contribute to innovation in the supply chain context: the management of knowledge; the management of information; the abilities to accommodate and manage technologies; and the ability to manage collaborative operations. In this paper, innovativeness is considered in the supply chain context since new processes introduce a tendency towards implementation of integrated information technology systems with supply chain partners in pursuit of more integrated supply chains and supply chain performance.…”
Section: Literature Review and Hypotheses Development 21 Innovativenessmentioning
confidence: 99%
“…In relation to conceptual skill, respondents had highlighted analytical thinking as a necessary skill (as supported by Larson, 2008) to be obtained. Having the skills to understand standard operating procedure (SOP) (see item number 6 in the "Skills" category) was perceived as important for logistics students (for example see Hyland, Soosay & Sloan, 2003). Respondents perceived that a familiarization with the SOP could be attained by attending industrial training or cooperative placement course.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Particularly in a SCM context, this implies continuous learning based on effective transfer of knowledge among supply chain partners (Bessant et al, 2003). In other words, the flexibility and agility required of companies operating in a turbulent supply chain environment can be increased through appropriate learning and training processes (Hyland et al, 2001). …”
Section: Supply Chain Learning and Ict Issues In The 3pl Industrymentioning
confidence: 99%
“…This has profound implications for learning needs in all supply chain companies (Hyland et al, 2001;Hult, et al, 2002). In recent years companies generally, and manufacturing companies specifically, have tended to concentrate on those activities which are regarded as core competencies.…”
Section: Introductionmentioning
confidence: 99%